2015
DOI: 10.1590/s1519-99402015000300021
|View full text |Cite
|
Sign up to set email alerts
|

Características quantitativas da carcaça de cordeiros Santa Inês, abatidos com diferentes espessuras de gordura subcutânea

Abstract: ResumoObjetivou-se avaliar as características quantitativas das carcaças de cordeiros da raça Santa Inês em confinamento, abatidos com três espessuras de gordura subcutâneas (EGS) diferentes. Foram utilizados 24 cordeiros, machos não castrados da raça Santa Inês, com aproximadamente 100 dias de idade e peso vivo de 22,7±3,75kg, divididos aleatoriamente em três tratamentos: abates com espessura de gordura subcutânea de 2,0; 3,0 e 4,0mm. O delineamento experimental adotado foi o inteiramente casualizado, com trê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 10 publications
4
10
1
9
Order By: Relevance
“…The slaughter age of lambs finished in feedlot and semi-feedlot in this experiment corroborates with the first two slaughter ages of feedlot Santa Inês lambs studied by Queiroz et al (2015), which were 145, 156 and 190 days, with live weight of 27.14, 33.84 and 34.85 kg, respecitvely. This indicates that the weight gain verified in this experiment fits the breed standards used, which are breedings that allow for higher meat production, muscle development and carcass conformation, being of great importance and capable of raising productivity in a shorter period of time.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The slaughter age of lambs finished in feedlot and semi-feedlot in this experiment corroborates with the first two slaughter ages of feedlot Santa Inês lambs studied by Queiroz et al (2015), which were 145, 156 and 190 days, with live weight of 27.14, 33.84 and 34.85 kg, respecitvely. This indicates that the weight gain verified in this experiment fits the breed standards used, which are breedings that allow for higher meat production, muscle development and carcass conformation, being of great importance and capable of raising productivity in a shorter period of time.…”
Section: Resultssupporting
confidence: 86%
“…Nevertheless, loin muscle and fat proportion were influenced by sex; females presented lower muscle proportions and higher fat proportions in relation to males (Table 5). Queiroz et al (2015) found a muscle, bone and fat proportion of 55.9, 20.9 and 23.6, res pectively, in male, uncastrated Santa Inês lambs slaughtered with a 3mm SFT. It is worth highlighting that the lambs were fed a high-concentrate diet, which favors a higher fat deposition in the carcass.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Estudos demonstram que, o GMD esperado em animais criados a pasto ou seja com maior teor de volumoso na dieta e suplementados é entre 150-200 g dia -1 (Carvalho et al, 2007;Fernandes et al, 2011;Ribeiro, 2010), enquanto cordeiros confinados, alimentados com maior proporção de concentrado, espera-se ganhos de 350-450 g dia -1 (Poli et al, 2008;Ribeiro et al, 2009 Tabela 3), pois os mesmos apresentaram crescimento uniforme das medidas de comprimento (comprimento corporal) e altura (altura de anterior e posterior). Queiroz et al (2015) observaram AOL de 10,6 ± 1,04 cm 2 para animais com 2 mm de ESPG, trabalhando com cordeiros Santa Inês com aproximadamente 100 dias de idade, alimentados com feno de aveia e concentrado a base de farelo de milho e soja.…”
Section: Resultsunclassified
“…Adicionalmente, para ovinos da raça Santa Inês o estudo relatado por (Queiroz et al, 2015) indica que animais com EGS de 3 mm proporcionaram melhores resultados para as características quantitativas da carcaça.…”
Section: Considerações Iniciaisunclassified